Impact of Segmented Magnetization on the Flagellar Propulsion of Sperm‐Templated Microrobots - Veronika Magdanz; Jacopo Vivaldi; Sumit Mohanty; Anke Klingner; Marilena Vendittelli; Juliane Simmchen; Sarthak Misra; Islam S. M. Khalil (Advanced Science, 2021)
Abstract Technical design features for improving the way a passive elastic filament produces propulsive thrust can be understood by analyzing the deformation of sperm‐templated microrobots with segmented magnetization. Magnetic nanoparticles are electrostatically self‐assembled on bovine sperm cells with nonuniform surface charge, producing different categories of sperm‐templated microrobots. Depending on the amount and location of the nanoparticles on each cellular segment, magnetoelastic and viscous forces determine the wave pattern of each category during flagellar motion. Passively propagating waves are induced along the length of these microrobots using external rotating magnetic fields and the resultant wave patterns are measured. The response of the microrobots to the external field reveals distinct flow fields, propulsive thrust, and frequency responses during flagellar propulsion. This work allows predictions for optimizing the design and propulsion of flexible magnetic microrobots with segmented magnetization.